Peningkatan Kemampuan Pemecahan Masalah Matematis Mahasiswa melalui Model Pembelajaran Group Investigation - Siregar, Tanti Jumaisyaroh (IAIN PADANGSIDIMPUAN, 2019)
The problem solving ability of students still low the problem of this research was mathematics. The purposes of this research was to know analyze improvement in mathematics problem solving ability of students that given group investigation learning with students that given direct learning. This type of research is a quasi-experimental research. The population in this study were all students of Mathematics Education Study Program UIN North Sumatra Medan and the samples were taken by cluster random sampling based on existing classes, namely PMM-4 class as an experimental class and PMM-2 as a control class. Data collection techniques in this study were using tests of students' mathematical problem solving abilities (pre tests and post tests) in the form of essay tests. The collected data is then searched for the N-gain value and analyzed using t test with SPSS 17 software.. Based of the results analysis, it showed that: Improvment of the students’ mathematics problem solving ability that given group investigation learning model was higher than the students’ mathematics problem solving abiliy that given direct learning. His then, suggested that group investigation learning model used for lectures to improved students’ mathematics problem solving ability.